Analisis pengukuran kinerja karyawan menggunakan metode Human Resource Scorecard (HRSC) di UPT Industri Kayu dan Produk Kayu Pasuruan - Maslikhan, Maslikhan; Masud, M Imron (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze employee performance measurements at the Pasuruan Timber and Wood Products UPTI using the Human Resource Scorecard (HRSC) method. The HRSC method is used as a holistic approach in evaluating employee performance by paying attention to financial aspects, customers, internal processes, as well as growth and learning. This research explores data through in-depth interviews and direct observation of HR management practices at UPTI. Data analysis was carried out to identify the main factors that influence employee performance in the organization using guidelines and metrics provided by HRSC. It is hoped that the research results can provide in-depth insight for the management of Pasuruan Wood and Wood Products UPTI in improving employee performance, identifying areas that need improvement, and increasing overall effectiveness. It is hoped that the findings from this research can become the basis for developing more effective human resource management strategies and can better support the achievement of organizational goals.